Community perspectives on maternal and child health during nutrition and economic transition in sub-Saharan Africa. Issue 12 (15th August 2021) - Watson, Daniella; Kehoe, Sarah H; Erzse, Agnes; Compaoré, Adélaïde; Debpuur, Cornelius; Nonterah, Engelbert A; Sorgho, Hermann; Norris, Shane A; Hofman, Karen J; Lawrence, Wendy; Newell, Marie-Louise; Godfrey, Keith M; et al.
Abstract: Objective: To explore community perceptions on maternal and child nutrition issues in Sub-Saharan Africa. Design: Thirty focus groups with men and women from three communities facilitated by local researchers. Setting: One urban (Soweto, South Africa) and two rural settings (Navrongo, Ghana and Nanoro, Burkina Faso) at different stages of economic transition. Participants: Two hundred thirty-seven men and women aged 18–55 years, mostly subsistence farmers in Navrongo and Nanoro and low income in Soweto. Results: Differences in community concerns about maternal and child health and nutrition reflected the transitional stage of the country. Community priorities revolved around poor nutrition and hunger caused by poverty, lack of economic opportunity and traditional gender roles. Men and women felt they had limited control over food and other resources. Women wanted men to take more responsibility for domestic chores, including food provision, while men wanted more involvement in their families but felt unable to provide for them. Solutions suggested focusing on ways of increasing control over economic production, family life and domestic food supplies. Rural communities sought agricultural support, while the urban community wanted regulation of the food environment. Conclusions: To be acceptable and effective, interventions to improve maternal and child nutrition need to take account of communities' perceptions of their needs and address wider determinants of nutritional status and differences in access to food reflecting the stage of the country's economic transition. Findings suggest that education and knowledge are necessary but not sufficient to support improvements in women's and children's nutritional status.